Design and validation of an automation strategy for the strip test process in the semiconductor industry - Rahman, Muhamad Arfauz A; Lin, Chengsi; Maropoulus, Paul G; Teoh, Woei Sheng; Rahman, Azrul Azwan Abdul; Mohamad, Effendi (2023)
The semiconductor devices may be individually tested or tested in a batch process. One type of batch process is strip testing. Strip testing is the electrical testing of a semiconductor while the device is still in the lead frame strip. Strip test offers the most cost savings for small devices and short test times. Despite their advantages, current strip testing is not a fully optimized solution. During the lot change, the operator must perform a series of system-to-physical validation and several steps of system tracking before the lot starts. Various manual activities are happening within the process, consuming many productivity issues. On top of that, human intervention during the process will increase the possibility of the quality issue. The research aims to investigate the current tasks during the strip test process. It also aimed to develop and validate a suitable automation strategy for the trip test process. The work starts with a detailed study of the current process, transaction, and hardware. Later a potential improvement using automation is proposed to replace the operator's repetitive job and simultaneously be fully integrated with the manufacturing execution system. This research is hoped to bring a significant contribution and readiness for the next level of automation in semiconductor manufacturing, especially in strip testing. Through automation functionality, this preliminary work shows an increase in productivity and quality upon implementation.